College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 2 - Functions and Graphs - Exercise Set 2.1: 95



Work Step by Step

Calculate each individual term: $\sqrt{f(-1)-f(0)}=\sqrt{3-(-1)}=\sqrt{4}=2,$ $[g(2)]^{2}=(-6)^{2}=36$ $f(-2)\div g(2)g(-1)=6\div(-6)\cdot 4=-1\cdot 4=-4$ $\sqrt{f(-1)-f(0)}-[g(2)]^{2}+f(-2)\div g(2)g(-1)=$ $= 2 -36 +(-4)$ $=-34-4$ $=-38$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.